2020
DOI: 10.3340/jkns.2018.0215
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Oblique Lateral Interbody Fusion at L5–S1 Level Compared to Transforaminal Lumbar Interbody Fusion

Abstract: The use of oblique lateral interbody fusion at the L5-S1 level (OLIF51) is increasing, but no study has directly compared OLIF51 and transforaminal lumbar interbody fusion (TLIF) at the L5-S1 level. We evaluated the usefulness of OLIF51 by comparing clinical and radiologic outcomes with those of TLIF at the same L5-S1 level. Methods : We retrospectively reviewed and compared 74 patients who underwent OLIF51 (OLIF51 group) and 74 who underwent TLIF at the L5-S1 level (TLIF51 group). Clinical outcomes were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Woods et al [ 3 ] retrospectively evaluated 137 patients who underwent the OLIF procedure, in which 10 patients who underwent OLIF51 only, and 84 patients who underwent OLIF25 combined with OLIF51; then, the author draws a conclusion that OLIF is a safe procedure at L1-5 as well as L5-S1. Mun et al [ 19 ] retrospectively reviewed and compared 74 patients who underwent OLIF51 and 74 who underwent TLIF51 and concluded that OLIF51 was more effective for indirect decompression of foraminal stenosis, providing strong mechanical support. Zairi et al [ 14 ] also showed the feasibility of accessing the L5-S1 level through the mini-open retroperitoneal approach without the need for ALIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woods et al [ 3 ] retrospectively evaluated 137 patients who underwent the OLIF procedure, in which 10 patients who underwent OLIF51 only, and 84 patients who underwent OLIF25 combined with OLIF51; then, the author draws a conclusion that OLIF is a safe procedure at L1-5 as well as L5-S1. Mun et al [ 19 ] retrospectively reviewed and compared 74 patients who underwent OLIF51 and 74 who underwent TLIF51 and concluded that OLIF51 was more effective for indirect decompression of foraminal stenosis, providing strong mechanical support. Zairi et al [ 14 ] also showed the feasibility of accessing the L5-S1 level through the mini-open retroperitoneal approach without the need for ALIF.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to LCIV is the most threatening complication associated with OLIF51 which can be very difficult to control once injured, and mobilization of these vascular structures is often a technically demanding procedure [ 15 , 23 ]. The injury to LCIV is also the most commonly complication observed in clinical practice [ 8 , 19 ]. This phenomenon is caused by the low iliocaval junction positions and the medially located LCIV, reducing the size of the operating field.…”
Section: Discussionmentioning
confidence: 99%
“…(3) retrospectively evaluated 137 patients who underwent OLIF procedure, in which 10 patients who underwent OLIF51 only, and 84 patients who underwent OLIF25 combined with OLIF51, then the author draws a conclusion that OLIF is a safe procedure at L1-5 as well as L5-S1. Mun et al (16) retrospectively reviewed and compared 74 patients who underwent OLIF51 and 74 who underwent TLIF51 and concluded that OLIF51 was more effective for indirect decompression of foraminal stenosis, providing strong mechanical support. Zairi et al (11) also showed the feasibility of accessing the L5-S1 level through the mini-open retroperitoneal approach without the need for ALIF.…”
Section: Application Of Olif51mentioning
confidence: 99%
“…(12,20) The injury to LCIV is also the most commonly complication observed in clinical practice. (5,16) This phenomenon is caused by the low iliocava junction positions and the medially located LCIV, reducing the size of the operating eld. According to reports in the literature, the vascular injury in the early result of OLIF was 8.6%, and it increases when the L5-S1 segment is involved.…”
Section: Simulation Of Olif51mentioning
confidence: 99%
“…Surgical treatment of pathologies at the lumbosacral junction is a common challenge in the everyday life of a spine surgeon. Anterior approaches to this junction serve as an alternative to transforaminal lumbar interbody fusion (TLIF), giving clinical, radiological, and biomechanical results superior to TLIF (Kapustka et al, 2019; Mobbs et al, 2015; Mun et al, 2020; Xu et al, 2018). The latest development in the anterior lumbar interbody fusion (ALIF) procedure is its application to the lateral position, allowing for simultaneous posterior percutaneous screw placement as a single level surgery at L5–S1, or as part of a multilevel procedure enabling surgeons to complete lumbar fusion procedures from L1 to S1 in a single lateral position (Drazin et al, 2015; Malham et al, 2019; Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%